Genotoxicity in vivo of phenazine and aminophenazines assayed in the wing spot test and the DNA-repair test with Drosophila melanogaster. - Watanabe, T.; Kasai, T.; Arima, M.; Okumura, K.; Kawabe, N.; Hirayama, T. (Mutation Research, 1996)
The genotoxicity and DNA-damaging activity of 6 phenazine and aminophenazine derivatives were assayed in the wing spot and DNA-repair tests in Drosophila melanogaster. Phenazine (Pz), and all aminophenazines tested, namely, 1-aminophenazine (APz), 2-APz, 2,3-diaminophenazine (DAPz), 2,7-DAPz and 2,7-diamino-3,8-dimethylphenazine (DADMPz), exhibited mutagenicity significantly in the wing spot test. The activities in the wing spot test were ranked in a sequence DADMPz > (2,7-DAPz, 2,3-DAPz) > (2-APz, 1-APz, Pz). In the DNA-repair test, 2,3-DAPz, 2,7-DAPz, and DADMPz clearly showed DNA-damaging activity, but Pz, 1-APz and 2-APz were inactive. Based on these results, we predict that DADMPz, 2,3-DAPz and 2,7-DAPz are likely to be more carcinogenic than 2-APz, 1-APz or Pz.